Prospective Hemophilia Inhibitor PUP Study reveals distinct antibody signatures during FVIII inhibitor eradication - Paul, Helmut; Berg, Verena; Gangadharan, Bagirath; Bowen, Joel; LeBeau, Petra; Blatný, Jan; Male, Christoph; Radulescu, Vlad C; Diaz, Rosa; Mancuso, Maria Elisa; Brown, Deborah L; Reipert, Birgit M (Blood advances, 2023)
Factor VIII (FVIII) inhibitor formation is a major clinical concern during replacement therapy in patients with hemophilia A. Immune tolerance induction (ITI) is the only therapeutic approach to attempt inhibitor eradication and establishment of long-term immune tolerance to FVIII. Hemophilia Inhibitor Previously Untreated Patient (PUP) Study (HIPS) was a prospective clinical trial to investigate changes in the immune system of PUPs with severe hemophilia A. Five patients who developed persistent FVIII inhibitors during HIPS entered an ITI extension arm (HIPS-ITI). During HIPS-ITI, inhibitor patients received ITI with the same FVIII product (a single source of recombinant, human full-length FVIII) used in HIPS until successful tolerance, declared failure, or a maximum of 2 years after HIPS-ITI enrollment, whichever came first. Blood samples and clinical data were collected monthly. Longitudinal FVIII-binding antibody signatures, associated binding specificities, and apparent affinities were determined for each patient at each sampling time point. ITI was successful or partially successful in 2 patients and failed in 3. Both groups presented with distinct FVIII-specific antibody signatures. ITI success required the disappearance of FVIII inhibitors, which was associated with the eradication or sustained titer minimization of high-affinity FVIII-specific antibodies, particularly of the immunoglobulin G1 (IgG1) and IgG4 subclasses. In contrast, ITI failure, as reflected by FVIII inhibitor persistence, was associated with persistent high-affinity FVIII-specific antibodies. Interestingly, 1 patient with partial ITI success and 1 patient with ITI failure developed apparent oligoreactive FVIII-binding antibodies during ITI. The explanation of the true nature of these antibodies requires more comprehensive follow-ups in future studies. This trial was registered at www.clinicaltrials.gov as #NCT01652027.
Keywords: Factor VIII; imunoglobulin G; faktor VIII; Hemophilia A; Immunoglobulin G; prospektivní studie; lidé; imunologická tolerance; Humans; Prospective Studies; hemostatika; Immune Tolerance; hemofilie A; Hemostatics